Corn-based bioplastic as seedling bag / Nur Nadia Nasir and Siti Amira Othman - Nasir, Nur Nadia; Othman, Siti Amira (2021)
Polyethylene bags have traditionally been used in the production of seedling bags, which are discarded in the soil or burned after transplantation due to the enormous amount of organic material connected to the bags, which is impossible to recycle or decompose. Furthermore, when a seedling is removed from its bag for transplant, there is a potential of root damage, which directly impacts the plant's growth. In this study, seedling bags that made from corn starch with filler (diammonium phosphate or potassium nitrate) to be used in plant seedling. Corn-based bioplastic offers a seedling bag that can be planted directly into the soil, do not required to transplant the plant, decompose naturally and also supply nutrients to plants. Which is it will reduce the risk of root damage and encouraging the plant's growth. Due to increasing public awareness around the world have opened up new market opportunities. Besides, with a similar feature with polyethylene bag, it's an ideal alternative in the sense of environmental sustainability and also compatibility.